Proton pump inhibitors and the risk of adverse cardiac events. - David N Juurlink; Colin R Dormuth; Anjie Huang; Chelsea Hellings; J Michael Paterson; Colette Raymond; Anita Kozyrskyj; Yola Moride; Erin M Macdonald; Muhammad M Mamdani (PLoS ONE, 2013)
Recent evidence suggests that proton pump inhibitors (PPIs) might be linked with adverse cardiac events, but a causal relationship is unproven.We applied the self-matched case series method to two studies using population-based health care data from Ontario, Canada between 1996 and 2008. The first included subjects aged 66 years or older hospitalized for acute myocardial infarction within 12 weeks following initiation of PPI, while the second included subjects hospitalized for heart failure. In both studies we designated the primary risk interval as the initial 4 weeks of therapy and the control interval as the final 4 weeks. To test the specificity of our findings we examined use of histamine H2 receptor antagonists and benzodiazepines, drugs with no plausible causal link to adverse cardiac events.During the 13-year study period, we identified 5550 hospital admissions for acute myocardial infarction and 6003 admissions for heart failure within 12 weeks of commencing PPI therapy. In the main analyses, we found that initiation of a PPI was associated with a higher risk of acute myocardial infarction (odds ratio 1.8; 95% confidence interval 1.7 to 1.9) and heart failure (odds ratio 1.8; 95% confidence interval 1.7 to 1.9). However, secondary analyses revealed similar risk estimates histamine H2 receptor antagonists and benzodiazepines, drugs with no known or suspected association with adverse cardiac events.PPIs are associated with a short-term risk of adverse cardiac events, but similar associations are seen with other drugs exhibiting no known cardiac toxicity. Collectively these observations suggest that the association between PPIs and adverse cardiac events does not represent reflect cause-and-effect.